Strong convergence theorems for generalized nonexpansive mappings with the system of equilibrium problems in banach spaces - Warunun Inthakon (2018)
In this paper, by using the shrinking projection method, we provestrong convergence theorems for finding a common element of the fixed pointsset of a generalized nonexpansive mapping and the set of common solutions of afamily of equilibrium problems with bifunctions defined on the dual space of aBanach space.